Present and future restaurant management competencies: an industry perspective - Vega, Daniel (Kansas State University, 2016)
Restaurant managers are responsible for the daily operation, coordination of staff, and profitability in the one million plus restaurants in the United States. However, the restaurant industry has a high management turnover rate and the identification of any process that may help restaurant owners identify, hire, and retain qualified managers is vital to the success of any operation, and the industry as a whole. Clearly identifying competencies that are needed for a manager to be successful might help in lowering the turnover rate and ensure that operations are successful. Not only will the identification of competencies benefit operators, it will also provide information for faculty in hospitality programs to build and adapt curriculum to meet the demands of industry. Few studies have focused on restaurant manager competencies and most are over 20 years old, and no studies have explored future competencies. Thus, the purpose of this study is to determine present and future restaurant management competencies. Specific questions include: 1. Which competencies are necessary for entry-level restaurant managers? 2. How will entry-level management competencies change in the next 10 years? 3. What is the magnitude of change between current and future restaurant manager competencies? The sample for this study included 123 restaurant managers in the United States, and yielded a 21.9% response rate. Most of the highest ranked competencies are soft skills. Managers ranked leadership skills as the most important competency, while education was ranked lowest. Interestingly, when exploring individual competencies, results of present compared to future competencies showed a slight decrease in mean score. Paired Samples T-tests were used to explore differences between present and future competencies and between the different domains. Few significant differences were found, though education was the only competency with a significantly higher future mean. Managerial implications, limitations, and directions for future studies are discussed.
Keywords: Competencies; Knowledge; Skills; Education; entry-level managersRestaurant Industry